2020
DOI: 10.1097/mpg.0000000000002816
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection in Pediatric Patients Living in Europe

Abstract: Objectives: The aim of the study was to assess clinical presentation, endoscopic findings, antibiotic susceptibility and treatment success of Helicobacter pylori (H. pylori) infected pediatric patients. Methods: Between 2013 and 2016, 23 pediatric hospitals from 17 countries prospectively submitted data on consecutive H. pylori-infected (culture positive) patients to the EuroPedHP-Registry. Results: Of 1333 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 40 publications
2
27
0
6
Order By: Relevance
“…The success rate of phenotype-guided tailored therapy in our study was 70.4% and did not achieve the target rate of > 90%. Our results are similar to those of a respective study published by Kori et al ( 10 ) which revealed an eradication rate of 79.8% after susceptibility-based treatment. A study in Belgium and one in Spain reported eradication rates of 72 and 78.7% in children with culture results ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The success rate of phenotype-guided tailored therapy in our study was 70.4% and did not achieve the target rate of > 90%. Our results are similar to those of a respective study published by Kori et al ( 10 ) which revealed an eradication rate of 79.8% after susceptibility-based treatment. A study in Belgium and one in Spain reported eradication rates of 72 and 78.7% in children with culture results ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 93%
“…Thirteen studies investigating the effectiveness of culture-based tailored therapy in children are shown in Table 1 . The eradication rate was over 90% in five studies ( 9 , 11 , 17 , 20 , 21 ) but ranged from 70 to 90% in the other eight studies ( 10 , 12 16 , 18 , 19 ). For the tailored therapy based on molecular tests with gastric biopsy, there is a paucity of data for children, though the eradication rate in most adult studies was over 90% ( 22 25 ).…”
Section: Introductionmentioning
confidence: 93%
“…Contrariwise, a study on Bulgarian children did not reveal any significant association between age and H. pylori infection [ 136 ]. Similar to most studies worldwide, the male gender was also reported to be a risk factor in European children [ 151 ]. Nevertheless, a recent study from Romania indicated that females were more prone to develop H. pylori -associated gastritis when compared to males in a cohort of children [ 152 ].…”
Section: H Pylori Peculiarities In Europasupporting
confidence: 77%
“…In the recently published analysis of the survey from 23 pediatric hospitals from 17 European Countries during the 2013–2016 period (EuroPedHP‐Registry), primary resistance to metronidazole was detected in 20.9% (95% CI: 18.4–23.5) and primary resistance to clarithromycin in 24.8% (95% CI: 22.1–27.5) of the strains from 1333 patients. Double resistance was detected in 5.8% of the strains 30 . In the same study, it is shown that in therapy naïve children, a 10‐day triple therapy tailored to antimicrobial susceptibility reached only 75.6% success and a 14‐day therapy 85% success in per protocol analysis.…”
Section: Discussionmentioning
confidence: 79%